Differential Expression of Hepatic Genes of the Greater Horseshoe Bat (Rhinolophus ferrumequinum) between the Summer Active and Winter Torpid States. - Yanhong Xiao; Yonghua Wu; Keping Sun; Hui Wang; Bing Zhang; Shuhui Song; Zhenglin Du; Tinglei Jiang; Limin Shi; Lei Wang; Aiqing Lin; Xinke Yue; et al. (PLoS ONE)
Hibernation is one type of torpor, a hypometabolic state in heterothermic mammals, which can be used as an energy-conservation strategy in response to harsh environments, e.g. limited food resource. The liver, in particular, plays a crucial role in adaptive metabolic adjustment during hibernation. Studies on ground squirrels and bears reveal that many genes involved in metabolism are differentially expressed during hibernation. Especially, the genes involved in carbohydrate catabolism are down-regulated during hibernation, while genes responsible for lipid β-oxidation are up-regulated. However, there is little transcriptional evidence to suggest physiological changes to the liver during hibernation in the greater horseshoe bat, a representative heterothermic bat. In this study, we explored the transcriptional changes in the livers of active and torpid greater horseshoe bats using the Illumina HiSeq 2000 platform. A total of 1358 genes were identified as differentially expressed during torpor. In the functional analyses, differentially expressed genes were mainly involved in metabolic depression, shifts in the fuel utilization, immune function and response to stresses. Our findings provide a comprehensive evidence of differential gene expression in the livers of greater horseshoe bats during active and torpid states and highlight potential evidence for physiological adaptations that occur in the liver during hibernation.